PENGARUH KEJELASAN SASARAN ANGGARAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DAERAH DENGAN SISTEM PENGENDALIAN INTERN SEBAGAI VARIABEL MODERASI - Frensly Loppies; Jefry Gasperz; Franco Limba (Jurnal Kajian Ekonomi dan Manajemen Indonesia (JKEMI), 2023)
This study aims to determine the effect of the clarity of budget targets on the performance accountability of government agencies with the internal control system as a moderating variable. This study uses primary data from respondents through questionnaires distributed to 44 Regional Apparatus Organizations (OPD) in Ambon, with a total of 132 respondents. Data analysis in this study used multiple linear regression analysis and moderated regression analysis using Moderated Regression Analysis (MRA). The results of simple regression analysis show that the clarity of budget targets has a significant effect on the performance accountability of government agencies, while the results of the MRA test show that the Internal Control System variable is not able to moderate the relationship between Clarity of Budget Targets and Performance Accountability of Government Agencies